How digital platforms improve teaching: comparing teacher performance across Peru - Medina-Bedón, Yurfa Carolina; Sumarriva-Bustinza, Liliana Asuncion; Arias Huánuco, Mery Jesús; Carlos-Yangali, Hugo Augusto; Espinoza-Herrera, Gladys Margarita; Araujo-Reyes, Luis Donato; Alfaro-Saavedra, Maura Natalia; Yauri-Huiza, Yeni; Pumacayo-Sanchez, Zaida Olinda; Madrid-Gómez, Karina Eddmy (International Journal of Evaluation and Research in Education (IJERE), 2025)
This study addresses the challenge of enhancing pedagogical content knowledge (PCK) performance among primary education teachers in Peru, particularly in the context of increasing reliance on digital platforms. With significant regional and demographic disparities in access to digital resources, this research aims to evaluate the effectiveness of digital platforms in supporting teaching practices. Using a quantitative, cross-sectional design, the study analyzed data from the 2022 national unique test (PUN), which assesses cognitive and pedagogical skills among teachers, and a digital platform integration questionnaire (DPIQ) administered to 2,000 teachers. The findings revealed a positive correlation between digital platform usage and PCK performance, with younger and female teachers demonstrating higher scores. Urban teachers also outperformed their rural counterparts, highlighting regional disparities in digital access. The study concludes that integrating digital platforms into teaching practices can enhance PCK performance, but there is a need for targeted professional development and investment in digital infrastructure, particularly in underserved areas. Addressing these disparities is crucial to ensuring that all teachers can benefit from digital advancements, ultimately improving educational outcomes.